2019
DOI: 10.3892/ol.2019.10134
|View full text |Cite
|
Sign up to set email alerts
|

RANBP9 suppresses tumor proliferation in colorectal cancer

Abstract: RAN binding protein 9 (RANBP9) is widely expressed in mammalian tissues, including osteosarcoma, lung, gastric and breast cancer tissues. However, currently, not much is known about the role of RANBP9 in colorectal cancer (CRC). In the present study, RANBP9 expression in CRC tissues and cell lines was measured by immunohistochemistry and western blotting, respectively. Subsequently, RANBP9 -short hairpin RNA (shRNA) and RANBP9 plasmids were constructed and transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Reduced expression of RANBP9 has been associated with distant metastasis and chemo-resistance in gastric cancer [44] . The silencing of RANBP9 in colorectal cancer cells also resulted in an increase of cell growth in vitro and tumorigenesis in vivo [45] . However, a straightforward cancer suppressive role is clearly inconsistent with the ability of RANBP9 to enhance Receptor Tyrosine Kinases or MAPK signaling [46][47][48][49] .…”
Section: Ranbp9 and Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Reduced expression of RANBP9 has been associated with distant metastasis and chemo-resistance in gastric cancer [44] . The silencing of RANBP9 in colorectal cancer cells also resulted in an increase of cell growth in vitro and tumorigenesis in vivo [45] . However, a straightforward cancer suppressive role is clearly inconsistent with the ability of RANBP9 to enhance Receptor Tyrosine Kinases or MAPK signaling [46][47][48][49] .…”
Section: Ranbp9 and Cancermentioning
confidence: 96%
“…While it remains unclear whether RANBP9's tumor suppressive effects is observed in vitro, most studies agree that RANBP9 is over-expressed in a variety of highly prevalent tumor types including that of NSCLC [44,45,[50][51][52] .…”
Section: Ranbp9 and Cancermentioning
confidence: 99%
“…The study by Qin et al recently reported that both RANBP9 mRNA and protein expression are increased in colorectal cancer compared to paired normal mucosa. However, in vitro and in xenografts from HCT116 and HT29 knockdown of RANBP9 resulted in increased proliferation [66].…”
Section: Ctlh Complex Members: Tumor Suppressors or Oncogenes? Drimentioning
confidence: 99%
“…Despite the in vitro evidence showing that knockdown of RANBP9 results in increased tumor cell proliferation, invariably, tumors of different types display higher levels of expression compared to the normal counterpart. This is true for lung cancer [65, 81], colorectal cancer [66], osteosarcoma [82], gastric cancer [64], and invasive breast cancer [83].…”
Section: Ctlh Complex Members: Tumor Suppressors or Oncogenes? Drimentioning
confidence: 99%
“…In our previous study, we found that RANBP9 was overexpressed in CRC tissues in a small patient cohort. It suppressed CRC cell proliferation both in vitro and in vivo ( 18 ). The aim of this study was to determine the association between RANBP9 expression levels and clinicopathological parameters in an expanded patient cohort, as well as CRC patient prognosis.…”
Section: Introductionmentioning
confidence: 99%